2005
DOI: 10.1208/aapsj070230
|View full text |Cite
|
Sign up to set email alerts
|

Fish drug analysis—Phish-pharm: A searchable database of pharmacokinetics data in fish

Abstract: Information about drug residues and pharmacokinetic parameters in aquatic species is relatively sparse. In addition, it is difficult to rapidly compare data between studies due to differences in experimental conditions, such as water temperatures and salinity. To facilitate the study of aquatic species drug metabolism, we constructed a Fish Drug/Chemical Analysis Phish-Pharm (FDA-PP) database. This database consists of more than 400 articles that include data from 90 species (64 genera) of fish. Data fields in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Databases containing metabolism and pharmacokinetics data for certain drugs are already available (18, 19), although Phenol-Explorer is the first to contain similar data for natural or dietary compounds and to allow all retrieved information to be traced back to the original publications. It is also unique in that all intervention studies have been systematically analyzed and relevant data comprehensively curated.…”
Section: Discussionmentioning
confidence: 99%
“…Databases containing metabolism and pharmacokinetics data for certain drugs are already available (18, 19), although Phenol-Explorer is the first to contain similar data for natural or dietary compounds and to allow all retrieved information to be traced back to the original publications. It is also unique in that all intervention studies have been systematically analyzed and relevant data comprehensively curated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, crystals can occlude renal tubules causing severe damages in kidney. Generally, fish absorb and excrete chemicals more slowly than mammals (Reimschuessel, 2008;Reimschuessel et al 2005Reimschuessel et al , 2009). The tissue half-life (t) in rainbow trout for MEL and CYA is 3-4 days and 1-2 days, respectively (Reimschuessel et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also shown other adverse effects on fish after ingestion of MEL and CYA, such as reduction of food consumption, body weight loss and histopathological alterations in kidney (Reimschuessel et al , 2009Xue et al 2011;Phromkunthong et al 2013). Moreover, little is known about the process of crystal removal in cold-blooded fish (Reimschuessel et al 2009(Reimschuessel et al , 2010, which absorb and excrete chemicals more slowly than mammals (Reimschuessel et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these parameters are included in the Phish-Pharm Database and should be considered when administering antibacterials to fish. Table 5 shows some drug dosages that have been reported for fish (Reimschuessel et al, 2005). It is important to realise that the dosages listed in Table 5 may not have been shown to be safe or effective in all fish species.…”
Section: Dosagementioning
confidence: 99%